2010
DOI: 10.1111/j.1464-410x.2010.09391.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring, fellowship training and academic careers of women urologists

Abstract: In conclusion, non-intervention is in certain cases, an appropriate approach for managing urinary tract calculi in all locations. If such a strategy is pursued patients must be made aware of the risks associated with it and the options for intervention if subsequently required. As in many other diseases, data from surveillance studies will better inform our ability to advise individuals. CONFLICT OF INTERESTNone declared. REFERENCES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…As mentioned above, one of the reasons for few residents choosing these subspecialties may be related to a lack of female mentors, such as female urological oncologists, in these areas of subspecialties 20 .…”
Section: Cuaj -Original Research Anderson Et Al Training Female Urolomentioning
confidence: 99%
“…As mentioned above, one of the reasons for few residents choosing these subspecialties may be related to a lack of female mentors, such as female urological oncologists, in these areas of subspecialties 20 .…”
Section: Cuaj -Original Research Anderson Et Al Training Female Urolomentioning
confidence: 99%
“…[1][2][3] Surveys of program directors of graduate medical education programs report the proportion of programs offering mentorship vary from 49% in US Internal Medicine programs 4 to 65% in Canadian postgraduate programs. 5 When mentoring programs are available, the mentoring activities are often loosely monitored and the outcomes poorly evaluated.…”
Section: Mentors Are Increasingly Recognized As Crucial Tomentioning
confidence: 99%
“…Just under half of respondents described their practice as being general urology. A total of 25% reported female urology as a sub‐speciality interest, compared with 24–45% of American Board of Urology‐certified urologists . A total of 7.5% of our respondents subspecialized in paediatrics compared with 10.4–19% of US women, while 7.5% of our respondents reported oncology as a subspecialty compared with 2.4–10% of US women urologists .…”
Section: Discussionmentioning
confidence: 75%
“…Job satisfaction rates were high, with the vast majority of our respondents reporting they were moderately or very satisfied with their practice. Other authors have also reported high satisfaction rates among women urologists .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation